Mindfulness and stress in the ultra trail runner - Rodríguez Ceberio, Marcelo (2024)
The field of sport psychology is gaining ground, becoming more and more integrated in the world of sport in general and in the world of ultra trail running in particular. Although this sport is booming, little is known about the psychological characteristics of these athletes, who dare to challenge long distances in extremely hostile natural terrain and riddled with obstacles. These challenges can lead, under certain conditions, ultra trail runners to be immersed in stress processes that, if prolonged over time, can turn into distress and lead to more suffering than enjoyment for an activity that, in the beginning, was chosen to develop. In order to counteract stress in the ultra trail runner, there are several strategies. In this paper, far from pretending to exhaust the existing possibilities, but simply to outline various proposals, we will take the contributions of a systemic view, cognitive behavioral therapies, contextual therapies and neurosciences applied to sport, from an eclectic perspective, embodied in multiple intervention strategies with athletes. Among the tools to be built with the athlete, Mindfulness will be presented as a resource that nourishes and amplifies psychology in general and sport psychology in particular, being considered a key for the specific practice of the athlete, as well as for his daily life.